Promoter orientation of the immunomodulatory Bacteroides fragilis capsular polysaccharide A (PSA) is off in individuals with inflammatory bowel disease (IBD). (3rd September 2019) - Blandford, Lucy E.; Johnston, Emma L.; Sanderson, Jeremy D.; Wade, William G.; Lax, Alistair J.
ABSTRACT: Bacteroides fragilis is a member of the normal microbiota of the lower gastrointestinal tract, but some strains produce the putative tumourigenic B. fragilis toxin (BFT). In addition, B. fragilis can produce multiple capsular polysaccharides that comprise a microcapsule layer, including an immunomodulatory, zwitterionic, polysaccharide A (PSA) capable of stimulating anti-inflammatory interleukin-10 (IL-10) production. It is known that the PSA promoter can undergo inversion, thereby regulating the expression of PSA. A PCR digestion technique was used to investigate B. fragilis capsular PSA promoter orientation using human samples for the first time. It was found that approximately half of the B. fragilis population in a healthy patient population had PSA orientated in the 'ON' position. However, individuals with inflammatory bowel disease (IBD) had a significantly lower percentage of the B. fragilis population with PSA orientated 'ON' in comparison with the other patient cohorts studied. Similarly, the putative tumourigenic bft- positive B. fragilis populations were significantly associated with a lower proportion of the PSA promoter orientated 'ON'. These results suggest that the proportion of the B. fragilis population with the PSA promoter 'ON' may be an indicator of gastrointestinal health.